(untitled) (Precision Medicine Communications, 2022)
Sanguesa et al., undertook an investigation to discern the differences in the levels of Clozapine (CLZ) in plasma and determine the pharmacogenetic and sociodemographic factors that influence it as well as introduce these tools in a clinical setting. In a group of 23 patients diagnosed with psychotic disorders CLZ concentration in plasma were measured alongside CLZ pharmacokinetic and pharmacodynamic parameters. Their findings revealed that smoking status, age, and weight were significantly associated with mean concentration/dose ratio (C/D). Gender and mean CLZ concentrations also demonstrated a significant difference. Smokers having the genotype rs762551 AA had a significantly lower C/D ratio. The authors concluded that measuring CLZ levels in plasma with pharmacogenetics as well as classical factors produced greater individualization of treatment. Per Med. 2022 May;19(3):181-192.